Transformasi Digital dan Perubahan Pola Interaksi Sosial Masyarakat: Studi Kasus di Kecamatan Menteng, Kota Jakarta Pusat - Nugroho, Dimas Arya; Rahmawati Putri, Siti (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
Digital transformation has significantly reshaped social interaction patterns in urban communities. Advances in information technology, social media, and digital devices have altered how individuals communicate, form social relationships, and engage with public spaces. This study aims to analyze the impact of digital transformation on changes in social interaction patterns in Menteng District, Central Jakarta. Using a qualitative approach with a case study design, data were collected through field observations, in-depth interviews, and document analysis. Thematic analysis was employed to examine changes in the form, intensity, and quality of social interactions. The findings reveal a shift from face-to-face interactions toward digitally mediated interactions, increasing communication efficiency while reducing emotional depth and relational quality. Social media has become a dominant platform for social networking, identity construction, and civic participation, but it also generates challenges such as superficial interactions, social polarization, and declining social cohesion. This study highlights the need for digital literacy and the revitalization of physical social spaces to maintain balanced social relations in the digital era.